Spatial link between Adélie penguin foraging effort and krill swarm abundance and distribution - Riaz, Javed; Bestley, Sophie; Wotherspoon, Simon; Cox, Martin J.; Emmerson, Louise (Frontiers in Marine Science, 2023)
Understanding how predator foraging behaviour is influenced by the distribution and abundance of prey is a fundamental aspect ofchallenge in marine foraging ecology. This is particularly relevant in Southern Ocean ecosystems where the functional relationships between select predator species and Antarctic krill (Euphausia superba) are used to guidecan inform ecosystem conservation and precautionary fisheries management. In this study, we examine the spatial associations between krill swarm characteristics and Adélie penguin (Pygoscelis adeliae) foraging effort at Béchervaise Island, a long-term monitoring site in East Antarctica. Spatially integrating two years of regional-scale krill acoustic data with contemporaneous horizontal and vertical movement information from chick-rearing adult Adélie penguins, we assessed how penguin foraging effort changed in relation to krill swarm abundance and distribution across the survey area. Our findings show that penguin diving effort was focussed in areas with a high number of krill swarms, yet they did not focus their effort in areas with high krill biomass. These results suggest the spatial organisation of Adélie penguin foraging effort can provide an indication of krill presence (and/or availability) but may not reflect krill abundance. We discuss our results in the context of penguin foraging strategies, capturing single krill within the water column rather than the engulfment feeding strategy of larger marine mammals such as whales. Our work substantially improves understanding of penguin-krill dynamics in East Antarctica and provides a greater level of nuance regarding the utility of Adélie penguins as indicator species under CCAMLR’s Ecosystem Monitoring Programme (CEMP). Understanding these predator-prey linkages will become increasingly important for managing any expanding krill fisheries in the region or changes in the prey field under future climate change scenarios. Thus, our results and can be interpreted alongside other ecological indicators to support management of the East Antarctic sector of the Southern Ocean ecosystem.